?EFFECT OF TEMPERATURE AND USE OF FERMENTED GREEN GRAM AS STARTER CULTURE ON THE PREPARATION OF FERMENTED FISH SILAGE (Biological Sciences - PJSIR, 1995)
Fermented fish silage was prepared at different controlled temperatures: 10°,20°,30° and 40°C. Samples were taken out at 0, 3, 7, 14and 21 days for determining changes in pH value, non protein or soluble nitrogen, peptides, ammonia, amino acid nitrogen and lactic acid bacterial (LAB) count. According to the findings of this study, the temperature hasaprofoundeffectonthequalityandthedurationoffermentationoffishsilage.Goodquality silagecan be prepared within3 days at40°,7 days at30°,14 days at20° and21days at lO°C.Meritsoffermented green gram as starter culture were also evaluated at these temperatures.